Influence of Social Media Usage on Generation Z’s Choice in Selecting Restaurants in Kathmandu - Shah, Prasiddhika; Bhusal, Navraj; Chettri, Keshab Khatri (Journal of Business and Social Sciences Research, 2023)
This paper examines the influence of social media usage on Generation Z’s choice in selecting a restaurant in the Kathmandu district. A hierarchical multiple regression model is used to examine the effect of the independent factors (perceived image, electronic word-of-mouth, sales promotion, and restaurant popularity) on the dependent variable (restaurant choice). The data is collected from Generation Z (Gen Z) residing in Kathmandu districts by adopting convenience sampling. The findings of this study suggest that the Gen Z residing in Kathmandu district tend to make restaurant choices based on their perceived image and electronic word-of-mouth (E-WOM), as indicated by the positive correlation and regression coefficients. On the other hand, despite showing a strong relationship in the correlation analysis, the regression coefficients of sales promotion and restaurant popularity do not seem to significantly impact consumers’ restaurant choice decisions among Generation Z of Kathmandu.